Dynamic adsorption of toxic indigo carmine dye on bio-inspired synthesised Fe3O4 nanoparticles: kinetic and thermodynamic study. Issue 5 (9th April 2022) - Patil, Suryakant A.; Kumbhar, Pramod D.; Patil, Sandip K.; Vadiyar, Madagonda M.; Suryawanshi, Umesh P.; Jambhale, Chitra L.; Anuse, Mansing A.; Kim, Jin H.; Kolekar, Sanjay S.
ABSTRACT: The bio-inspired synthesis of Fe3 O4 nanoparticles using a common kitchen waste, Bengal gram bean ( Cicer arietinum L.) extract (BGBE) for enhanced adsorption of toxic indigo carmine dye is reported. Synthesised adsorbent was characterised by FTIR, FE-SEM, XRD, BET and XPS to understand its meticulous properties. The Fe3 O4 adsorbent shows fascinating surface area of 78.61 m 2  g −1 with a pore volume of 0.25 cc g −1 at P/P0  = 0.98 and displayed nanograin like morphology. The efficiency towards adsorption of toxic IC dye was found up to 99.71 ± 0.35% within 40 min at pH 7 with 0.25 g of Fe3 O4 nanomaterials having the 299 ± 2 K surrounding temperature. The Langmuir monolayer adsorption capacity was found to 393.7 mg g −1 at the stroke speed 150 rpm. The experimental data follows the Freundlich adsorption isotherm. Kinetically the uptake rate of IC dye follows pseudo-second-order kinetic model. The thermodynamic study reveals that IC dye adsorption process is spontaneous and endothermic in nature.